METHODS FOR ASSESSING THE EFFECTIVENESS OF PSYCHOLOGICAL TRAINING OF PERSONNEL OF MILITARY UNITS TO PERFORM TASKS FOR THE INTENDED USE - Pasichnik V. І.; Afanasenko, V. S. (Honor and Law, 2019)
The essence of the concept of “effectiveness of psychological preparation” and approaches to its evaluation are concretized; the main criterion and indicators of the effectiveness of psychological preparation; the urgency of the development, the theoretical foundations and the content of the methodology for the expert evaluation of the effectiveness of the psychological training of the personnel of the military unit for the fulfillment of tasks by designation are disclosed.